PELAKSANAAN PASAL 8 DAN 9 PERATURAN DAERAH KOTA PONTIANAK NOMOR 11 TAHUN 2022 TENTANG PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA (STUDI DI JALAN DAYA NASIONAL PONTIANAK) - NIM. A1011191304, MUHAMMAD FARHAN BAGUS PRASETYA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Street Vendors are business actors who carry out trading activities using movable or immovable business facilities, using city infrastructure, social facilities, public facilities, land and buildings owned by the government and/or private sector that are temporary/non-permanent. Arrangement and Empowerment of Street Vendors is an effort made by the regional government through the determination of fostered locations to determine, move, organize and eliminate locations by paying attention to public interests, social, aesthetics, health, economy, security, order, environmental cleanliness and in accordance with laws and regulations so that they are able to grow and develop both the quality and quantity of their businesses. The formulation of the problem in this thesis is